Optimal Allocation of Dynamic VAR Support Using Mixed Integer Dynamic Optimization - Tiwari, Ashutosh; Ajjarapu, Venkataramana (IEEE transactions on power systems, 2011)
Dynamic security of power systems is a major concern during contingencies, especially in present environment when there is inadequate transmission line capacity and dynamic reactive power support. This paper addresses dynamic VAR allocation to ensure acceptable transient voltage performance and short-term stability against severe contingency. To filter out severe contingency, severity indices are proposed. An algorithm based upon trajectory sensitivity analysis is used to select candidate VAR locations. The overall problem is formulated (in dynamic framework) as mixed integer dynamic optimization (MIDO). To solve MIDO problem, it is converted into mixed integer nonlinear problem (MINLP) by complete discretization using simultaneous discretization approach. The effectiveness of proposed approach is illustrated using New England 39-bus system.